2014
DOI: 10.1216/jca-2014-6-2-173
|View full text |Cite
|
Sign up to set email alerts
|

Positive margins and primary decomposition

Abstract: We study random walks on contingency tables with fixed marginals, corresponding to a (log-linear) hierarchical model. If the set of allowed moves is not a Markov basis, then there exist tables with the same marginals that are not connected. We study linear conditions on the values of the marginals that ensure that all tables in a given fiber are connected. We show that many graphical models have the positive margins property, which says that all fibers with strictly positive marginals are connected by the quad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The answer to this question is negative. More than a year after first submission of the present paper, Kahle, Rauh, and Sullivant showed that the global Markov ideal of K 3,3 is not radical [20].…”
Section: Introductionmentioning
confidence: 73%
“…The answer to this question is negative. More than a year after first submission of the present paper, Kahle, Rauh, and Sullivant showed that the global Markov ideal of K 3,3 is not radical [20].…”
Section: Introductionmentioning
confidence: 73%
“…A first step toward Problem 17.17 was developed in [KRS12]. There the authors study only the connectivity of F b as a function of the position of b in the cone Q + A. Additionally all ideals there are radical, and consequently the subtleties of mesoprimary decomposition play no role.…”
Section: Posets Of Mesoprimesmentioning
confidence: 99%
“…In algebraic statistics, decompositions of binomial ideals give insight into how a set of conditional independence statements among random variables can be realized [DSS09, HHH + ]. More generally, the connectivity of lattice point walks in polyhedra can be analyzed using decompositions of binomial ideals [DES98,KRS12]. These applications rely on decompositions of unital ideals-generated by monomials and differences of monomials-into unital ideals; these are mesoprimary decompositions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in some cases, a smaller set of moves suffices under the condition of positive margins, for example, Chen et al49 and Hara et al50 demonstrate this in case of exact logistic regression. More recently, Kahle et al51 have studied the positive margin property and its generalization called the interior point property for graphical models by studying primary decompositions of conditional independence ideals.…”
Section: Computing Markov Basesmentioning
confidence: 99%